Perlindungan Hukum Atas Harta Waris Bagi Penderita Down Syndrome Dalam Perspektif Hukum Islam (Studi Kasus Pengadilan Negeri Medan Nomor 102/Pdt.P/2019/Pn.Mdn) - Nurdailamy; Suaib Lubis (Journal Smart Law, 2025)
This study aims to determine how legal protection for the inheritance rights of people with Down Syndrome is viewed in Islamic law and Indonesian law, as well as to explain the forms of protection that can be provided and the obstacles faced in its implementation. The method used is normative legal research by examining legislation, Islamic law books, and interviews with families and religious leaders in Langkat Regency. The results of the study show that people with Down Syndrome still have full rights to their parents' inheritance, and the state provides protection through the appointment of a legal guardian who is responsible for managing the child's assets and meeting their living needs. Legal protection can be provided through the appointment of a guardian in court, the creation of a will, and the registration of assets in the name of the child with Down Syndrome. However, its implementation still faces several obstacles, such as a lack of legal certainty, difficulties in appointing guardians, and limited public knowledge about the rights of persons with disabilities. This study emphasizes that legal protection for children with Down Syndrome is a shared responsibility between families, the government, and religious institutions so that justice can be realized in accordance with Islamic teachings and applicable laws.